Rhodamine B as a long‐term semi‐quantitative bait marker for wild boar. (1st June 2017) - Baruzzi, Carolina; Coats, Julia; Callaby, Rebecca; Cowan, Dave P.; Massei, Giovanna
ABSTRACT: Wild boar and feral pigs ( Sus scrofa ) are increasing worldwide and baiting campaigns to deliver vaccines and toxicants are often undertaken to control their populations or the diseases they transmit. In these campaigns, it is important to assess bait uptake by the target species. We investigated the use of the systemic marker Rhodamine B (RB) to detect multiple episodes of bait uptake by wild boar. Rhodamine B is widely used in wildlife studies as a bait marker incorporated in hair, but it is still poorly studied in suids. We analyzed the detection of RB bands in different hair types of wild boar fed multiple RB‐treated baits at different intervals in summer and fall. We calculated the minimum number of hairs and whiskers required to detect RB bands. Captive wild boar consumed RB‐treated baits (ranging in dose from 1.3 mg/kg to 17.0 mg/kg of wild boar body mass) in summer and autumn. The time between consecutive episodes of RB‐treated bait ingestion was 4 days, 9 days, 2 weeks, and 3 weeks. We collected hairs and whiskers 7, 18, 25, 39, 49, 94, 103, 110, and 124 days after feeding boar with RB‐treated baits. Feeding wild boar RB‐treated baits 4 and 9 days apart did not produce separate RB bands. Two to 3 weeks were sufficient for separate RB bands to appear in 17.8% of hairs and 27.0% of whiskers. The minimum number of hairs to detect RB bands was 3 for shoulder hairs and 2 for whiskers, mane, and flank hairs. Mane hairs had the fastest growth rate, and there was no difference among the growth rate of other hairs and whiskers. We suggest that a minimum of 2 mane hairs and 2 whiskers should be sampled to be 95% confident that RB bands can be detected in wild boar that have consumed RB‐treated baits. © 2017 The Wildlife Society. Abstract : Bait markers are widely employed during baiting campaigns and Rhodamine B is one of the most commonly used bait markers. We investigated Rhodamine B detection in wild boar hair and found distinct fluorescent bands visible in 17.8% of hairs and 27.0% of whiskers when the marked baits were given to the animals 2 or 3 weeks apart.